VIRTUAL REALITY AND INCLUSIVE EDUCATION: A FRAMEWORK FOR TRANSFORMATION - Mahajan, Monica Mahajan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Inclusive education is increasingly recognized as a cornerstone of equitable learning, yet traditional pedagogical methods often fail to accommodate the diverse needs of all learners especially those with special educational needs (SEN). This paper explores the transformative role of Virtual Reality (VR) in addressing these challenges by offering immersive, interactive, and adaptable learning experiences. Framed within Constructivist Learning Theory, Experiential Learning Theory, and the SAMR Model, the study critically examines how VR fosters engagement, supports differentiated instruction, and enhances both cognitive and emotional development. It categorizes VR modalities non-immersive, semi-immersive, fully immersive, and mixed reality and aligns these with practical applications for inclusive learning environments. Platforms such as ClassVR, Floreo, Labster, and CoSpaces Edu are examined for their efficacy in promoting empathy, executive functioning, and life skills development among diverse learners. The paper also addresses critical ethical and logistical considerations, including equitable access, educator readiness, health and safety, and data privacy. Ultimately, this study highlight the potential of VR to serve as a powerful enabler of inclusive education when implemented with intentionality, accessibility, and pedagogical integrity.